Technology Based Learning Innovations in Social Sciences Education - Riswan Djaenudin; Hudaidah Hudaidah; L.R. Retno Susanti; Dwi Hasmidyani (Universitas Sriwijaya, 2025)
Technology is transforming education in today’s digital era by making learning easier, faster, and more engaging. This allows students to understand material better and access education anytime and anywhere. This study employs a qualitative descriptive approach with a One-Group Pretest-Posttest design. Data were collected, processed, and analyzed using a narrative method to explore the impact of technology on student learning. The findings show that the use of the Electronic Document Management System (EDMS) in learning increased students’ average scores from 64.28 to 89.8, representing a 25.5% improvement. This indicates that teknologi helps students learn more effectively and participate more actively. The novelty of this research, EDMS is the innovative tool in social sciences education, demonstrating its effectiveness in improving learning outcomes and student engagement in a digital learning environment. Therefore, this research provides insight into how technology significantly supports the advancement of education in universities.